Agenda
039-0015-001 BASQUE CHILDREN'S COMMITTEE MEETING TO BE HELD AT 5 P.M., ON MONDAY, NOVEMBER 7TH, 1938, at the Council of Action, Horseferry House, Horseferry Road, S.W. AGENDA 1. Apologies for absence. 2. Minutes of last meeting. 3. Matters arising on the minutes. (a). Home for older boys in Catalonia. i. Report by Dr. Audrey Russell. ii. Suggested appointment of Mr Angus McCowen. (b). Mrs. Wood. 4. Repatriation. (a). Report from Centres. (b). Mr. Ewald's report. (c). Spanish Government Decree. (d). Request from Birmingham. (e). Letters from Mlle. Ferriere and Mr. Thackrah. (f). Recommendations from Sub-Committee with regard to repatriation. 5. Minutes of Basque Administrative Sub-Committee. 6. Matters arising on the minutes. 7. Larrinaga. 8. Closing of Leicester and Bristol Homes. 9. Any other business. 10. Date of next meeting. 292/946/39/15